Varicella zoster meningoencephalitis without exanthem: immunocompetent host - shafaq saleem; Tariq, Hafiz Muhammad Motsim (Journal of the Pakistan Medical Association, 2024)
In an immunocompetent person, varicella zoster virus (VZV) is an uncommon cause of aseptic meningoencephalitis. Reactivation of the latent varicella zoster virus from nerve infection results in shingles, a condition marked by rash, intense pain, and dermal involvement in immunocompromised hosts. We present an unusual case of a 22-year-old immunocompetent male diagnosed as VZV meningoencephalitis without exanthem. Workup revealed no risk factors for contracting VZV nor was there any childhood history associated with it. The patient responded to the treatment given and became symptom-free thereafter. Keywords: Varicella meningoencephalitis, Aseptic meningitis, Acyclovir, Immunocompetent, Varicella vaccines.